Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan E-Commerce : (UMKM Kota Sukabumi) - Fitri Sri Nuraeni; Risma Nurmilah; Acep Suherman (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
Developments in the field of technology as well as advances in the business world have encouraged Micro, Small and Medium Enterprises actors to innovate in services related to the use of e-commerce technology. This research was conducted with the aim of examining whether each of the factors of cost efficiency, innovation and trust affect the tendency of MSMEs to adopt e-commerce. Data collection was carried out using a questionnaire with sample selection using a purposive sampling method, namely SMEs in Sukabumi City. The analysis used using quantitative methods. The test results show that each of the cost efficiency factors has a negative effect on the use of e-commerce and the innovation factor has a positive effect on the use of e-commerce and also the trust factor has a positive effect on the use of e-commerce. Questionnaires are distributed directly to MSMEs and focused SMEs that use e-commerce. This study did not conduct in-depth research on each application of the variables tested. With this research, MSMEs are more aware and concerned about the importance of e-commerce in their business because currently people prefer to shop online